Simplified Beam Element Model of Badminton Batting Process Based on Motion Differential Equation. (25th June 2021) - Li, Yingda
Abstract : Badminton is not only a traditional sport in China, but also an advantage sport in China. It has good entertainment, appreciation, and exercise, as well as a very broad mass base in China. Badminton racket as the key equipment of badminton, its production and design has a very critical impact on the development of the sport; the current existing research lacks the analysis of badminton batting moment. In order to more intuitively and clearly understand the force and displacement relationship of the racket net at the moment of badminton hitting, this study is based on the differential equation of motion, combined with the finite element analysis method to build a simplified beam element model. In order to verify the reliability of the model, the displacement of the beam element and the rod element of the badminton racket under the same load is constructed. Through the research results, it can be seen that the beam element model is more reliable for the numerical calculation of badminton batting moment. The in-depth analysis of badminton batting process has a certain reference significance for the production and design of badminton racket.